Report of the committee of the General Assembly, at their special session, August 25, 1812 : On that part of His Excellency the Governour's speech, which relates to his correspondence with the Secretary of War, &c. - Goddard, Calvin, 1768-1842 (Printed by Walter & Steele, 1812)
Report of the Committee of the Connecticut General Assembly, during its special session of August 1812, concerning correspondence of governor and the Secretary of War. The committee reviewed the details regarding the governor's refusal to order the state militia into the service of the United States, along with resolutions and declarations of the Assembly.